CULTURAL PRACTICES IN TEACHING PORTUGUESE FOR FOREIGNERS - Coutinho Sossolote, Cassia Regina [UNESP]; Aquino Martins, Flavia Maria de; Vivaldo, Leonardo Vicente [UNESP]; Muzzeti, Luci Regina [UNESP]; Suficier, Darbi Masson [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
The article entitled Cultural Practices in Teaching Portuguese for Foreigners aims to disseminate teaching practices facing the language teaching to students from Guinea Bissau or whom the Portuguese of Portugal is the official language. We seek to problematize the course given to those students with the purpose of appropriating the resources of expression for approval in subjects who were enrolled in Brazil in the first half of undergraduate Letras course in a higher education institution.
Keywords: Teachers' work and teaching practices; Cultural practices; Conceptions of language teaching; Relationship content and methodology; Literacy